Introduction to clinical psychology an evidence-based approach - Hunsley, John 1959-; Lee, Catherine M. (Catherine Mary) 1955- (John Wiley & Sons, Inc., 2014)
"With well over half a century of experience in clinical psychology, Hunsley and Lee's Introduction to clinical psychology, 2nd edition provides clinical psychologists with an up-to-date resource that focuses on the scientific method and those clinical practices that are supported by research. This text offers important opportunities to contextualize clinical practice. Issues of diversity are examined while demonstrating how practice differs in populations of different ages. Current case studies are presented to provide a real-world perspective, while engaging Viewpoint boxes highlight fascinating and important debates."-- Publisher's description.